2023
DOI: 10.1051/bioconf/20237504002
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Pharmacokinetics Study of 2,5-Dibenzylidenecyclopentanone Analogs as Mono-Ketone Versions of Curcumin

Prajona Marbun,
Arief Rahman Hakim,
Navista Sri Octa Ujiantari
et al.

Abstract: The absorption-distribution-metabolism-excretion (ADME) profile is a crucial parameter that indicates the pharmacokinetics of the drug. The pharmacokinetic properties of a drug represent the fate of the drug in the body. Curcumin is a main compound in turmeric produced by plants of the Curcuma longa species, and has several pharmacological effects in animal and human clinical studies. However, preclinical and clinical studies have shown that curcumin has pharmacokinetic limitations such as poor bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…The molecular docking process investigated the interaction between four proteins and the active component in TIP-Heal. The docking procedure used in this study was a rigorously verified process, comprising the production of both ligands and proteins, validation of posture and score, and validated outcomes (54). The results showed that among the compounds examined (PubChem 5319898, 3-epiursolicacid, alpha-linoleic, and palmitic acid), PubChem CID 5319898 had the highest affinity towards the four selected proteins while showing a weaker effect towards the MMP-9 protein.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular docking process investigated the interaction between four proteins and the active component in TIP-Heal. The docking procedure used in this study was a rigorously verified process, comprising the production of both ligands and proteins, validation of posture and score, and validated outcomes (54). The results showed that among the compounds examined (PubChem 5319898, 3-epiursolicacid, alpha-linoleic, and palmitic acid), PubChem CID 5319898 had the highest affinity towards the four selected proteins while showing a weaker effect towards the MMP-9 protein.…”
Section: Discussionmentioning
confidence: 99%